Faktor-Faktor Yang Berhubungan Dengan Minat Wanita Usia Subur (WUS) Dalam Melakukan Inspeksi Visual Asam Asetat (IVA) Di Puskesmas Pondok Betung Kota Tangerang Selatan - Fahim Martina; Risza Choirunissa; Rini Kundaryanti (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Cervical cancer is the fourth type of cancer that most often affects women. One of the prevention efforts is by using the IVA test method. The results of a preliminary study at the Pondok Betung Health Center in Tangerang City in 2021 only 11 women took the IVA Test even though the target to be achieved was 100%. To find out the factors related to the interest of Women of Reproductive Age (WUS) in Visual Inspection of Acetic Acid (IVA) at the Pondok Betung Health Center, South Tangerang City. The design of this research is a quantitative analytic study with a cross sectional design. The population taken in this study were all Married Women of Reproductive Age (WUS) aged 25-45 years who were in the working area of the Pondok Betung Health Center, South Tangerang City in October 2022 with a total of 336 respondents. Sampling in this study using a purposive sampling technique to 183 respondents. The results of the univariate study showed that most women of childbearing age received information 68.9%, did not receive husband's support 56.3%, supported by good health workers 73.8%, access to health services < 3 km 68.9% , did not experience a history of sexually transmitted diseases 59.0% and were not interested in conducting early detection of cervical cancer using the Acetic Acid Visual Inspection (IVA) method 62.3% The results of the bivariate study showed that there was a relationship between sources of information (p value 0.000), husband's support (p value 0.000), support from health workers (p value 0.000), access to health services (p value 0.000), and a history of sexually transmitted diseases (p value 0.004 ). The support of health workers has a high probability of WUS' interest in carrying out an IVA test with an OR of 47.701. Keywords : Interest in Women of Reproductive Age (WUS), Visual Acetic Acid (IVA) Inspection.